Performance of Indonesian manufacturing companies: Economic value-added approach - Betty Tjandra; Dwi Sulistyorini; Rizky Mulia; Titi Anggraeni; Farah Margaretha Leon (Jurnal Inovasi Ekonomi, 2022)
This study aims to measure the company's performance based on Economic Value Added (EVA). The independent variables are Investment Capital, Return on Assets, Fixed Assets, Rate of Return on Fixed Assets, and Level Debt. This study uses data from 25 manufacturing companies listed on the Indonesia Stock Exchange over the 2016-2019 period. This study shows a significant negative effect of Investment Capital and Debt Level on EVA. The variable rate of return on fixed assets has a substantial impact on EVA, and there is no significant effect of the return on assets and fixed assets on EVA. Thus, it is expected that financial managers can increase profits and reduce debt to increase EVA.